Review of 2022 American College of Rheumatology (ACR) guideline for the prevention and treatment of glucocorticoid-induced osteoporosis: what’s new? - N. V. Toroptsova; E. L. Nasonov (Научно-практическая ревматология)
Glucocorticoids (GC) have been used in medicine since the middle of the twentieth century, including for the treatment of various systemic rheumatic diseases. However, long-term use of GC may be accompanied by the development of serious complications, one of which is secondary osteoporosis, leading to low-energy fractures, which affects the quality of life of patients and may lead to an increased risk of death. This article presents an overview with a discussion of the new edition of the guideline of the American College of Rheumatology (ACR) 2022 for the prevention and treatment of glucocorticoid-induced osteoporosis in adult patients.